Attitudes and perceptions of girls in St John's College about the practice of virginity testing - Swaartbooi-Xabadiya, Zolisa Cynthia (University of Limpopo (Medunsa Campus), 2010)
Background Virginity testing is a practice that has stimulated lots of discussions amongst people from various perspectives. Controversies around this practice have necessitated further research in order to bring the voice of girls into the virginity testing debate. Aim and objective The aim of the study was to explore perceptions and experiences of girls on the practice of virginity testing. Methodology Triangulation of qualitative data collective method was used. The researcher informally engaged in key informants’ interviews with stakeholders who participate in the practice attended virginity testing celebration to observe the proceedings and processes conducted during the practice. Focus group discussions were conducted. Data was analyzed using NVIVO. Results Elders, in particular mothers, encouraged participation of girls in virginity testing. Girls observed and sighted benefits, ranging from viz: HIV/STI prevention, societal recognition and acceptance, purity before marriage and delay of sexual debut. Non participation was attributed to the in availability of virginity testing practices the areas. Concerns of doggy behaviors by testers, uneducated testers of testers, compromised health standards were discussed. Conclusions These findings reveal that there are areas of misunderstanding on how the practice is viewed and represented in the media. Arguments against virginity testing seem to be based on the perspective of on Westernized, feminist and individualistic notions of humanity disregarding the social construction of traditional cultural practices. Socialization and moral standards of people from a particularly Western orientation dominate the debate against virginity testing with no basis that is supported by research.
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Attitude; Perception; Virginity testing